Teaching as if learning matters : pedagogies of becoming by next-generation faculty - Robinson, Jennifer Meta, 1962-; O'Loughlin, Valerie Dean; Kearns, Katherine; Plummer, Laura (Scholarship of teaching and learning., 2022)
"Teaching is an essential skill in becoming a faculty member in any institution of higher education. Yet how is that skill actually acquired by graduate students? Teaching as if Learning Matters collects first-person narratives from graduate students and new PhDs that explore how the skills required to teach at a college level are developed. It examines the key issues that graduate students face as they learn to teach effectively when in fact they are still learning and being taught. Featuring contributions from over thirty graduate students from a variety of disciplines at Indiana University, Teaching as if Learning Matters allows these students to explore this topic from their own unique perspectives. They reflect on the importance of teaching to them personally and professionally, telling of both successes and struggles as they learn and embrace teaching for the first time in higher education"--